Evaluation of Groundwater Quality Using Water Quality Indices in Parts of Lagos-Nigeria - Akoteyon, Isaiah S. (Journal of Environmental Geography, 2013)
Water samples collected from forty-five hand dug wells and thirteen boreholes using random sampling technique were measured for pH, electrical conductivity and total dissolved solids. Calcium, chloride, bicarbonate and carbonates were analyzed using titrimetry method. Magnesium, potassium and sodium by Atomic Absorption Spectrophotometer (AAS) and sulfate was analyzed using a spectrophotometer. The study aims to evaluate groundwater quality using water quality indices in parts of Lagos-Nigeria. The sample locations and spatial variations in the concentration of bicarbonates, Revelle and Water quality indices were mapped using surfer 6.0 software. The result shows that pH indicate extremely acidic to strongly alkaline condition, EC shows medium and high enrichment of salts from location 28 and 21 respectively. Spatially, about 31% and 29.3% of bicarbonate are under poor and moderate zones respectively. The computed Revelle index shows that 41.4% and 1.7% are slightly and strongly influenced by groundwater salinization respectively. Unlike the water quality index, about 12.1% and 1.7% indicate poor and water unfit for drinking respectively. The paper concludes that groundwater salinization is on the increase since over half of the samples are influenced by salinity. Unlike the water quality, it was concluded that the water is of good quality since about 86.2% is suitable for drinking purposes. Based on these findings, it was recommended that waste water treatment and disposal methods should be avoided and appropriate treatment methods to make it more potable and fit for human consumption should be employed in critical locations of the study area.